Millimeter-Wave Antennas: Configurations and Applications - du Preez, Jaco; Sinha, Saurabh (Signals and Communication Technology,, 2016)
This book comprehensively reviews the state of the art in millimeter-wave antennas, traces important recent developments and provides information on a wide range of antenna configurations and applications. While fundamental theoretical aspects are discussed whenever necessary, the book primarily focuses on design principles and concepts, manufacture, measurement techniques, and practical results. Each of the various antenna types scalable to millimeter-wave dimensions is considered individually, with coverage of leaky-wave and surface-wave antennas, printed antennas, integrated antennas, and reflector and lens systems. The final two chapters address the subject from a systems perspective, providing an overview of supporting circuitry and examining in detail diverse millimeter-wave applications, including high-speed wireless communications, radio astronomy, and radar. The vast amount of information now available on millimeter-wave systems can be daunting for researchers and designers entering the field. This book offers readers essential guidance, helping them to gain a thorough understanding based on the most recent research findings and serving as a sound basis for informed decision-making. .